Extraction the essential oil of clove plant Dianthus caryophyllus and studying its chemical composition (Latakia University Journal -Biological Sciences Series, 2024)
The flower buds of dianthus caryophyllus carnation plant were collected from the nursery of the Faculty of Agricultural Engineering at Tishreen University in Latakia during 2022/2023, the essential oil was isolated from samples taken using the Clevenger device, and the chemical content of the components of the essential oil of dianthus caryophyllus carnation plant was studied using a gas chromatography - mass spectrometer (GC-MS) device. Extraction using the Clevenger apparatus for the flower buds of the chervil plant gave an aromatic oil of light yellow color. The analysis of the essential oil using the GC\MS device showed the quantitative diversity of chemical compounds, which accounted for 99.9% of the total essential oil. The results of the (GC/MS) analysis showed the presence of 13 peaks within the chart, which indicates the presence of 13 chemical compounds ranging in percentage from 1.3% to 21.3 %, and the main compounds were as follows :Butylated hydroxytoluene, oleic acid, 3,4-hexandiol, 2,5-dimethyl  , Propanamide, 1,2-Ethanediamine,N-(2-aminoethyl), 1,6:3,4-Dianhydro-2-deoxy-β-d-lyxo-hexopyranose, Octadecane, 1-(ethenyloxy , Glycinamide, N(2)-methyl - , (2S,3S)-(-)-3-Propyloxiranemethanol. Where the compound Butylated Hydroxytoluene was the main component of the essential oil with 21.3%, followed by the compound Oleic Acid with 14.7%, followed by the compound 3,4-Hexanediol, 2,5-dimethyl - with 10.5%.